Accident rates in Poland’s foodstuff industry from the perspective of occupational safety management in the European Union - A. Zielińska; W. Bajdur (Global Journal of Environmental Science and Management)
The issue of accidents at work and accident prevention have a significant impact regarding safety, health protection and work environment management for the European Union. Work conditions need to be improved in Poland. Solving this collective issue caused by humanitarian as well as economic considerations is a primary mission in businesses. Creating more quality jobs is one of the main goals of the EU’s social policy. Health and safety in the work environment are essential conditions for work quality. This article presents the incidence of work-related accidents in the EU. In the 28 member states of the EU (EU-28), 2015 recorded over 3.2 million workplace accidents which invoked at least 4-day work leaves and 3,876 deaths. The authors of this analysis present the issue of workplace accidents based on the examination of incidents in large foodstuff plants of the Lodz voivodship i.e. food processing businesses that have been continuously active for the five year period of 2008-2012. The food industry belongs to one of the most fundamental economic fields and is one of the most important factors of economic growth and amounts to about 20% of domestic production in the processing industry in Poland. The Lodz province has been chosen on account of its central location in the country. For the selected group of businesses, there is a marked increase of workplace accidents – from 258 in 2008, to 333 incidents in 2012 – for the study period in that the lowest incidence occurred in 2009 (211 accidents), and the highest in 2011 (358 accidents).